INCOME ANALYSIS AND CONSTRAINTS OF BROILER CHICKEN BUSINESS IN DEWANTARA DISTRICT, ACEH UTARA REGENCY (CASE STUDY IN UD. KARYA CIPTA) - M. Shia Alam Banna; Jamilah Jamilah; Murdani Murdani (Jurnal Mahasiswa Agribisnis, 2022)
Livestock business is part of the development of the agricultural sector which has strategic values, among others in providing food needs. The purpose of this study were to determine the constraints of broiler business in Gampong Ulee Reuleung, Dewantara Sub-district, Aceh Utara District. The research methods used are quantitative and qualitative descriptive analysis. The results showed that the gross income and the net income obtained by UD.Cipta Karya broiler chicken business are Rp 43,290,000,- and Rp.2.263,362,91,- in production process. The R/C ratio of 1.05 and the B/C ratio of 0.05. Therefore it can be concluded that the broiler chicken business UD. Cipta Karya is feasible and profitable. Generally that the constraints faced by UD Karya Cipta broiler chicken business are seeds, capital, labor and climate.